2020
DOI: 10.3390/app10186303
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Problem-Solution Co-Evolution in the Context of Team Conceptual Design Activity

Abstract: The conventional prescriptive and descriptive models of design typically decompose the overall design process into elementary processes, such as analysis, synthesis, and evaluation. This study revisits some of the assumptions established by these models and investigates whether they can also be applied for modelling of problem-solution co-evolution patterns that appear during team conceptual design activities. The first set of assumptions concerns the relationship between performing analysis, synthesis, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 93 publications
(173 reference statements)
1
13
0
Order By: Relevance
“…Therefore, it is not surprising that numerous works aimed at studying (Alsager Alzayed et al, 2019) and supporting design space expansion through the use of, for example, heuristics (Daly et al, 2012) or computational tools (Gero and Kumar, 1993;Han et al, 2018). Relatedly, several studies explored the rate at which the design space expands in a team setting (e.g., Gero and Kan, 2016;Martinec et al, 2020). For this purpose, studies utilised a cumulative graph of issues' occurrences.…”
Section: Design Space Expansionmentioning
confidence: 99%
“…Therefore, it is not surprising that numerous works aimed at studying (Alsager Alzayed et al, 2019) and supporting design space expansion through the use of, for example, heuristics (Daly et al, 2012) or computational tools (Gero and Kumar, 1993;Han et al, 2018). Relatedly, several studies explored the rate at which the design space expands in a team setting (e.g., Gero and Kan, 2016;Martinec et al, 2020). For this purpose, studies utilised a cumulative graph of issues' occurrences.…”
Section: Design Space Expansionmentioning
confidence: 99%
“…It conceptualises the design process as two notional spaces ('problem space' and 'solution space') interacting with each other until both are firmly defined (Maher and Poon, 1996). Problem space constitutes from problem entities like requirements, constraints, and needs, while solution space consists of solution entities like conjectures, concepts, and working principles (Martinec et al, 2020). According to co-evolution, a potential solution can be resulted from interpreting the problem, labelled as problem space to solution space transition.…”
Section: Conjecture-based Problem Explorationmentioning
confidence: 99%
“…The authors' initial efforts of modelling team conceptual design activity (Martinec et al, 2019) have resulted in theoretical developments of a state-transition model and initial empirical evidence of designing patterns that can be identified using the model. The follow-up study (Martinec et al, 2020) delved deeper into the data and found correlations between proportions of different types of design operations as well as the most probable sequences of design operation pairs during team design activities. Here presented study builds on these qualitative and quantitative insights, primarily by adding the temporal aspect into modelling of proportions and sequences of design operations across the problem and the solution space.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, evaluation has been defined as a state transition resulting in the assessed appropriacy of a particular design entity within the explored design space. Please consult Martinec et al (2020) for more detailed definitions. The developed state-transition model thus enables capturing of various sequences of ASE design operations performed within and in-between the problem and the solution space during design activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation